A new species of Rhochmopterum Speiser (Diptera: Tephritidae: Tephritinae: Schistopterini) from India - Hatwar, Nikhil Khemrajji; David, Karamankodu Jacob; Hancock, David Lawrence; Raghuraman, Mahadevan; Gracy, Ramasamy Gandhi; Srinivasa, Narayana (Zootaxa, 2025)
A new species of Rhochmopterum Speiser is described and illustrated from India, namely Rhochmopterum malaviyai Nikhil, David & Hancock, sp. nov. from northeastern and northern plains of India. A key to all species of Rhochmopterum from Oriental region is included. mt-COI and 28s sequences of Rhochmopterum malaviyai Nikhil, David & Hancock, sp. nov. were obtained and reported.